An Effective Supervision Guide for Supervisors: A Systematic Approach to Organizing Data Generated During Monitoring Sessions in Student Teaching - Ocansey, R. (Physical Educator, 1988)
Student teacher supervisors can use the Effective Supervision Guide to facilitate the organization of data generated from monitoring student teachers. The guide's components include: baseline performance; behaviors needing remediation; remediation strategies; evaluation criteria; and commencement and completion dates for remediating behaviors. (CB)
Research Article
Keywords: Student; teacher; supervisors; performance